Can talent policy promote firm innovation: An empirical analysis from solar photovoltaic industry in China - Zhang, Yuanbo; Qu, Shiyou; Gao, Pengbin (Frontiers in Energy Research, 2023)
Supported by government policies, the innovation of China’s solar photovoltaic industry has been triggered greatly. As an important part of public policy, various talent policies have been issued to increase support for innovation. Therefore, it is essential to study the relationship between talent policy and firm innovation of Chinese solar photovoltaic industry. However, there is less empirical research on this topic. In this context, this study examined whether talent policy influences firm innovation. To examine the underlying causal mechanism, this study explored the role of human capital quality structure and human capital function structure in the relationship between talent policy and firm innovation. Based on the buffering and bridging mechanism of resource dependence theory, an empirical model of talent policy, human capital structure and firm innovation were conceptualized. Using an unbalanced panel data of 101 listed firms of the solar photovoltaic industry in China from 2008 to 2021, the random effect GLS regression was employed to empirically test the impact of talent policy on firm innovation, the mediating effects of human capital quality structure and human capital function structure, and examined the heterogeneous impact of nature of property rights and R&D intensity on the above relationships. The results show that talent policy can significantly promote firm innovation. Human capital structure plays mediating effects on the relationship between talent policy and firm innovation. Moreover, the talent policy and human capital structure’s effects on firm innovation are more significant in non-state-owned firms and firms with low R&D intensity. This study provides an important reference for promoting firm innovation through human capital structure in the construction of the talent policy.